Can a six-week exercise intervention improve gross motor function for non-ambulant children with cerebral palsy? A pilot randomized controlled trial. (February 2013) - Bryant, Elizabeth; Pountney, Terry; Williams, Heather; Edelman, Natalie
Objective: To determine the effect of a six-week exercise intervention on gross motor function for non-ambulant children with cerebral palsy. Design: A parallel arm randomized controlled trial. Setting: Four special schools. Participants: Thirty-five children aged 8–17 with bilateral cerebral palsy; Gross Motor Function Classification System levels IV–V. Method: Participants were randomly allocated to a static bike group, a treadmill group or control group. Participants in the bike and treadmill groups received exercise training sessions, three times weekly for six weeks. The control group received their usual care. Blinded assessments were performed at baseline and six weeks and followed up at 12 and 18 weeks. Outcome measures: Gross Motor Function Measures GMFM-66, GMFM-88D and GMFM-88E. Results: At six weeks significant differences were found in GMFM-88D scores between the bike group and the control group, and the treadmill group and the control group ( P < 0.05). The mean change (SD) in GMFM-88D score was 5.9 (6.8) for the bike group; 3.7 (4.4) for the treadmill group and 0.5 (1.9) for the control group. No significant differences were found for GMFM-66 or GMFM-88E scores between the bike group and control group, or the treadmill group and control group, although trends of improvement were observed for both exercise groups. The improvements observed declined during the follow-up period. Conclusion: This study provides preliminary evidence that exercising on a bike or treadmill may provide short-term improvements in gross motor function for non-ambulant children with cerebral palsy. This needs to be tested in a large-scale randomized trial.